Pure neuritic leprosy: Resolving diagnostic issues in acid fast bacilli (AFB)-negative nerve biopsies: A single centre experience from South India - Hui, Monalisa (Ann Indian Acad Neurol, 2015)
BACKGROUND AND PURPOSE: Demonstration of lepra bacilli is essential for definite or unequivocal diagnosis of pure neuritic leprosy (PNL) on nerve biopsy. However, nerves always do not show bacilli owing to the changes of previous therapy or due to low bacillary load in tuberculoid forms. In absence of granuloma or lepra bacilli, other morphologic changes in endoneurium and perineurium can be of help in making a probable diagnosis of PNL and treating the patient with multidrug therapy. MATERIALS AND METHODS: Forty-six biopsies of PNL were retrospectively reviewed and histologic findings were compared with 25 biopsies of non leprosy neuropathies (NLN) including vasculitic neuropathy and chronic inflammatory demyelinating polyneuropathy (CIDP). The distribution of endoneurial infiltrate and fibrosis, perineurial thickening, and myelin abnormalities were compared between PNL and NLN biopsies and analyzed by Chi-square test. RESULTS: Out of 46 PNL casses, 24 (52.17 %) biopsies were negative for acid fast bacilli (AFB). In these cases, the features which favor a diagnosis of AFB-negative PNL were endoneurial infiltrate (51.1%), endoneurial fibrosis (54.2%), perineurial thickening (70.8%), and reduced number of myelinated nerve fibers (75%). INTERPRETATION AND CONCLUSION: Nerve biopsy is an efficient tool to diagnose PNL and differentiate it from other causes of NLN. In absence of AFB, the diagnosis of PNL is challenging. In this article, we have satisfactorily evaluated the various hisopthological features and found that endoneurial inflammation, dense fibrosis, and reduction in the number of myelinated nerve fibers are strong supportive indicators of PNL regardless of AFB positivity.